E-Learning Based on Cloud Computing - Wu, Wei; Plakhtii, Anastasiia (International Journal of Emerging Technologies in Learning (iJET), 2021)
Modern technological paradigms of learning give educators an ability to support the development of highly professional human resources. For this reason, teachers of higher educational institutions find advanced technologies more and more useful. Rapid introduction of cloud computing into pedagogical practice creates a professional need to study the technological capabilities of cloud-based learning services to select the best educational solutions among available variants. In view of this, the current article provides a theoretical overview of e-learning cloud architecture layers and models of its deployment in the education system. In order to test the adaptability of learning management systems (LMSs) to a collaborative distance learning model, research among educators of I.M. Sechenov First Moscow State Medical University (Russia), Prydniprovska State Academy of Civil Engineering and Architecture (Ukraine) and Wuxi Institute of Technology (China) was carried out using the Blackboard Learn LMS as a case study. This study involved 100 individuals who tested the Blackboard Learn teaching capabilities. The conducted investigation allowed outlining the main advantages of the use of computer-based e-learning applications in the process of organizing and supporting the educational process. Among them are convenient means of processing educational content, effective educational process organization, effective tools for knowledge monitoring, and effective security and confidentiality system. The present work also shed light on the benefits of introducing cloud-based e-learning in higher educational institutions, as producers of an integrated educational product. The study confirmed that the introduction of cloud computing in education results in the advancement of the training content and can considerably improve students’ academic results due to updated learning technologies, concepts, and tools.